Memories and Records: Thoughts on The Vaccine Archive - Kwon, Vicki Sung-yeon; Sritharan, Lathika (Imaginations)

(untitled) (York University, 2020)
Vicki Sung-yeon Kwon, an art historian and curator, and Lathika Sritharan, a public health researcher, discuss their collaborative project Memories and Records: The Vaccine Archive, an archive display of vaccine-related memories and immunization records of people from various parts of the world. They share challenges and accomplishments of collaborating with multidisciplinary participants and mounting an art exhibition at the UNAIDS building. As Canadians of Asian ethnic and cultural background, Kwon and Sritharan contemplate how vaccines are differently remembered in the Global North and the Global South.